Adiabatic rapid passage in quantum dots: phonon‐assisted decoherence and biexciton generation. Issue 9 (31st May 2013) - Gawarecki, K.; Lüker, S.; Reiter, D. E.; Kuhn, T.; Glässl, M.; Axt, V. M.; Grodecka‐Grad, A.; Machnikowski, P.; Ulrich, Sven M.; Jetter, Michael; Michler, Peter
Abstract We study the evolution of a quantum dot controlled by a frequency‐swept (chirped), linearly polarized laser pulse in the presence of carrier‐phonon coupling. The final occupation of the exciton state is limited both due to phonon‐induced transitions between the adiabatic spectral branches and because of phonon‐assisted transitions to the biexcitostate. When the biexciton shift is large enough, the quantum dot can be modeled as a two‐level system, which corresponds to excitation with circularly polarized light. For this case, we compare different methods of simulations: (i) a time convolutionless method, (ii) correlation expansion and (iii) path integrals. We show that results obtained from these methods agree perfectly at temperatur. (© 2013 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)